2008
DOI: 10.1103/physrevb.77.180402
|View full text |Cite
|
Sign up to set email alerts
|

Correlation effects in the electronic structure of theMn4molecular magnet

Abstract: We present joint theoretical-experimental study of the correlation effects in the electronic structure of (pyH)3[Mn4O3Cl7(OAc)3]·2MeCN molecular magnet (Mn4). Describing the many-body effects by cluster dynamical mean-field theory, we find that Mn4 is predominantly Hubbard insulator with strong electron correlations. The calculated electron gap (1.8 eV) agrees well with the results of optical conductivity measurements, while other methods, which neglect many-body effects or treat them in a simplified manner, d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
325
4
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(358 citation statements)
references
References 52 publications
27
325
4
2
Order By: Relevance
“…All calculations are done using the generalized gradient approximation (GGA-PBE) [23] which is more suitable for the description of graphene-adatom chemical bonds [22] and systems with few hydrogen bonds [24]. Full optimization of all atomic positions was performed.…”
Section: Computational Methods and Used Modelsmentioning
confidence: 99%
“…All calculations are done using the generalized gradient approximation (GGA-PBE) [23] which is more suitable for the description of graphene-adatom chemical bonds [22] and systems with few hydrogen bonds [24]. Full optimization of all atomic positions was performed.…”
Section: Computational Methods and Used Modelsmentioning
confidence: 99%
“…It is suggested that under conditions of finite temperature, structures similar to C 10 may become energetically favorable. 38 Fig . 4 shows that amongst all energetically favorable configurations, the employed exchange correlation functionals predict C 1 and C 2 to be less stable than C 3 -C 9 .…”
Section: B Stability Analysis and Structural Propertiesmentioning
confidence: 99%
“…A wide band gap of about 3.5 eV has been observed experimentally 49 and calculated theoretically. 38,41,50 Numerous studies have already been conducted on hydrogen atoms adsorbed on single layer graphene but there is little information about hydrogen on bilayer graphene. A possible reason for this could be the failure of the standard GGA-PBE functional to correctly describes the vdW forces binding the layers of the bilayer graphene structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been presented in the literature that adsorption of H atom on graphene lattice can induce a magnetic moment about 1µ B , and possibly to be ferromagnetic when two H atoms are located on the same sublattice of graphene, [140][141][142] but a pair of hydrogen atoms that are located on the different sublattices of graphene cannot induce magnetic moment. 143,144 The Fermi level is moved upward from the graphene Dirac point, 145 due to electron transfer from H atoms, which saturating the open ends of the sheet. Fig.…”
Section: Graphene Modelmentioning
confidence: 99%